Au Pairs' Lives in Global Context
XIII, 273 p.
Keywords: Far from being the preserve of middle-class women from Northern Europe, au pairing is now booming worldwide. This collection, the first dedicated entirely to examining the lives of au pairs, traces their experiences across five continents showing how this form of domestic labour and childcare is thriving in the twenty-first century.